The External Communication Network of Al Jam’iyatul Washliyah and Its Role in Social Development in Labuhanbatu Utara - Silaen, Mulkan Darajat; Kholil, Syukur (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2025)
This study investigates the external communication network of Al Jam’iyatul Washliyah in Labuhanbatu Utara and examines its strategic contribution to advancing social development. It focuses on how Alwasliyah establishes, sustains, and leverages communication channels with various external stakeholders, including local governments, civil society organizations, and religious communities. Employing a qualitative case study methodology, data were gathered through in-depth interviews, direct observation, and document analysis. The findings demonstrate that Alwasliyah implements both formal and informal communication strategies grounded in mutual trust, cultural sensitivity, and Islamic values. These approaches are instrumental in fostering collaborative relationships, expanding program outreach, and enhancing public receptivity. Despite these strengths, the organization continues to face significant obstacles, such as limited communication infrastructure, bureaucratic inertia, and internal fragmentation among Muslim groups. The study concludes that communication practices which are adaptive, inclusive, and value-oriented are critical for Islamic organizations seeking to play a meaningful role in localized social transformation.